PENGARUH DEBT TO ASSET RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON EQUITY PADA PERUSAHAAN MANUFAKTUR SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BEI 2016 - 2020 - Willy Kumala Sari; Rahma BR Purba; Anggi Pratama Nasution (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This study aims to determine whether DAR and DER have an effect on ROE simultaneously and partially on ROE in manufacturing companies in the food and beverage sector listed on the IDX. This type of research is quantitative. The population in this study amounted to 26 companies and the sample in this study amounted to 9 companies. The results of this study indicate that DAR has a positive and significant effect on ROE with a tcount of 2.298 > 2.010. DER has a positive and significant effect on ROE with a tcount value of 2, > 2,010. Nilai Fhitung value of 8.402 > F tabel 3,19 with a significant 0.001 <0.05 then Ha is accepted. This means that there is a jointly significant effect of all independent variables Debt to Asset Ratio and Debt to Equity Ratio to the dependent variable Return on Equity. R Square value of 0.244 percentage of the influence of Debt to Equity Ratio and Debt to Assets Ratio on Return on Equity the remaining 75.6 is influenced by other variables such as net profit margin, stock prices and others.Keywords: DAR, DER, ROE.